License to Retaliate: Good Deeds as a Moral License for Misdeeds in Reaction to Abusive Supervision. Issue 2 (15th March 2022) - Liang, Lindie H.; Coulombe, Claudie; Skyvington, Sarah; Brown, Douglas J.; Ferris, D. Lance; Lian, Huiwen
ABSTRACT: Abusive supervision research demonstrates that subordinates often engage in deviance following abuse despite the negative consequences of doing so. Drawing on moral licensing theory, we propose that the relationship between abusive supervision and deviance is moderated by the extent to which subordinates perform positive voluntary work behaviors. We further suggest that moral disengagement moderates this moral licensing effect and that this relationship will hold when controlling for social exchange principles. In Study 1, we found that the relationship between abusive supervision and organizational deviance was strengthened by high organizational citizenship behavior (OCB) and was not significant at low levels of OCB. In Study 2, we found that the moral licensing effect was strengthened in individuals with a propensity to morally disengage, even when controlling for negative reciprocity beliefs and social exchange orientation. Implications for moral licensing and abusive supervision research are discussed.